2023
DOI: 10.1186/s12935-023-03059-6
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific peptidase 5 facilitates cancer stem cell-like properties in lung cancer by deubiquitinating β-catenin

Chia-Hao Tung,
Jia-En Wu,
Meng-Fan Huang
et al.

Abstract: Background Lung cancer has the highest mortality rate in the world, and mounting evidence suggests that cancer stem cells (CSCs) are associated with poor prognosis, recurrence, and metastasis of lung cancer. It is urgent to identify new biomarkers and therapeutic targets for targeting lung CSCs. Methods We computed the single-sample gene set enrichment analysis (ssGSEA) of 1554 Reactome gene sets to identify the mRNA expression-based stemness index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…This study showed significant advancements and characteristics in the regulation of CSC activity by the NR5A2 gene [ [46] , [47] , [48] , [49] , [50] ]. First, we used the OCLR algorithm and immune score to fully reveal the expression pattern of NR5A2 in patients with LUAD and systematically elaborated its regulatory mechanism on CSC activity.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed significant advancements and characteristics in the regulation of CSC activity by the NR5A2 gene [ [46] , [47] , [48] , [49] , [50] ]. First, we used the OCLR algorithm and immune score to fully reveal the expression pattern of NR5A2 in patients with LUAD and systematically elaborated its regulatory mechanism on CSC activity.…”
Section: Discussionmentioning
confidence: 99%
“…The deubiquitination is closely related to Wnt/β-catenin pathway and that many regulators have been found to mediate the ubiquitination level of β-catenin, including lncRNA PKMYT1AR [ 99 ], FABP7 [ 121 ], and USP5 [ 122 ] (Table 2 ). Of them, the PKMYT1AR/miR-485-5p/PKMYT1 axis inhibits ubiquitin-mediated degradation of β-catenin, which in turn promotes CSC maintenance and enhances tumorigenesis in NSCLC [ 99 ].…”
Section: The Positive Regulators Of Wnt/β-catenin Signalingmentioning
confidence: 99%
“…USP5 encodes ubiquitin-specific peptidase 5, one of the deubiquitinating enzymes remove ubiquitin from target proteins. USP5 directly interacts with β-catenin, leading to deubiquitination, stabilization of β-catenin in NSCLC cells [ 122 ].…”
Section: The Positive Regulators Of Wnt/β-catenin Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large amount of patients have received clinical treatment, they still experience poor prognosis due to drug resistance, recurrence, or metastasis, which is attributed to the presence of CSCs. Compelling evidence has uncovered that tumor progression is intricately associated with the existence of CSCs within the tumor bulk, including LUAD, ovarian cancer, hematologic tumors, and so on [ 11 , 12 ]. CSC-like phenotypes also play important roles in metastasis, recurrence, and other malignant phenotypes, which can be characterized by several methods including spheroid formative capacity, stem cell marker expression, tumorigenic potential, and increased invasiveness [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%